PELATIHAN E-LEARNING MENGGUNAKAN PLATFORM MOODLE SEBAGAI UPAYA MENINGKATKAN PROFESIONALISME GURU - Dedi Nurjamil; Zulpi Miftahudin (Universitas Trisakti, 2020)
Mathematics learning is directed at learning that can be done anytime and anywhere. Such learning can be done by conducting learning that is connected to the internet with the e-learning platform. For e-learning teacher use platforms can be used as learning media so that mathematical learning can be done anywhere. Researchers see that teachers especially teachers in junior high schools have difficulty in using e-learning in learning. This has an impact on students' understanding that is not optimal because teachers only rely on learning in the classroom. Service methods used are: 1) receiver theory and practice of e-learning 2) assignment of e-learning applications 3) evaluation of which e-learning has been applied inside outside the classroom. The results of this activity were that the trainees were seen to be motivated by 87% being received motivated, the remaining 13% were less motivated by the existence of this activity, then the response after the activity percentage that gave a positive response was 93% and 7% gave a less positive response. Another result is that most of the 15 teachers at SMPN 3 and 5 have used e-learning using either the google classroom or using moodle.